Ovarian Cancer: Prevention, Detection, and Treatment of the Disease and its Recurrence. Molecular Mechanisms and Personalized Medicine Meeting Report. (1st October 2012) - Modugno, Francesmary; Edwards, Robert P.
Abstract : Objective: To review the current understanding of the underlying molecular, biologic, and genetic mechanisms involved in ovarian cancer development and how these mechanisms can be targets for prevention, detection, and treatment of the disease and its recurrence. Methods: In May 2012, we convened a meeting of researchers, clinicians, and consumer advocates to review the state of current knowledge on molecular mechanisms and identify fruitful areas for further investigations. Results: The meeting consisted of 7 scientific sessions ranging from Epidemiology, Early Detection, and Biology to Therapeutics and Quality of Life. Sessions consisted of talks and panel discussions by international leaders in ovarian cancer research. A special career development session by the Congressionally Directed Medical Research Program Department of Defense Ovarian Cancer Academy as well as an oral abstract and poster session showcased promising new research by junior scientists. Conclusions: Technological advances in the last decade have increased our knowledge of the molecular mechanisms involved in a host of biological activities related to ovarian cancer. Understanding the role these mechanisms play in cancer initiation and progression will help lead to the development of prevention and treatment modalities that can be personalized to each patient, thereby helping to overcome this highly fatal malignancy.